Partisipasi Masyarakat Dalam Pengembangan Cagar Budaya Candi Pari Sebagai Situs Bersejarah Kabupaten Sidoarjo - Berlian Novianti Suseno; Akhmad Qomaru Zaman (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This research is based on community participation in the development of the cultural heritage of Candi Pari as a historical site in Porong District, Sidorajo Regency. The purpose of this study is to examine community participation in the development of Candi Pari cultural heritage. Finding efforts to increase community participation in the development of Candi Pari cultural heritage. This study used qualitative research methods with data collection techniques using interviews, observation, and documentation. The results of this study reveal that community participation in the development of Pari Temple cultural heritage as a historical site in Porong District, Sidoarjo Regency has been going well to date, one form of the implementation of the development of Pari Temple cultural heritage, one of which is through community participation in the development of Pari Temple cultural heritage. Efforts to increase community participation in the development of Candi Pari cultural heritage maintain the value of mutual cooperation in community participation through social activities. Community participation in the development of Pari Temple cultural heritage still involves the community around Pari Temple cultural heritage.